Adsorption studies of toxic cadmium(II) and chromium(VI) ions from aqueous solution by activated black cumin (Nigella sativa) seeds. Issue 4 (August 2020) - Thabede, Patience Mapule; Shooto, Ntaote David; Xaba, Thokozani; Naidoo, Eliazer Bobby
Abstract: Few studies that reported on black cumin seeds (BS) showed that the material has good adsorption capacity towards metal ions. Therefore, it is fair to conduct further studies on the material. However, literature survey shows that no previous study on black cumin seeds has reported on the effect of phosphoric acid (H3 PO4 ) and potassium permanganate (KMnO4 ) activating agents on the removal of toxic cadmium Cd(II) and chromium Cr(VI) ions from aqueous solution. Pristine black seeds were designated (PBS), the H3 PO4 and KMnO4 activated seeds (H3 BS) and (KMBS) respectively. The seeds were characterized by SEM, BET, XRD and FTIR. SEM micrographs revealed that H3 BS and KMBS were more porous than PBS. The BET surface area of H3 BS and KMBS increased to 10.3 and 9.30 m 2 /g respectively. FTIR spectra confirmed the presence of OH, COOH, CO and NH2 functional groups attached to the surface of all adsorbents. Adsorption batch studies revealed that the adsorption capacities of all adsorbents increased with increase in the concentration of Cd(II) and Cr(VI) in solutions. The isotherm data revealed that Cd(II) and Cr(VI) ions removal uptake onto all adsorbents found good fit for Langmiur. This implies that the uptake processes occurred on active sites having equal affinity and further suggest monolayer adsorption. It was observed that all adsorbents had higher uptake for Cd(II) than Cr(VI) ions. It was found that the maximum adsorption capacity for Cr(VI) ions was 17.70 mg/g at pH 1 and temperature 353 K whilst for Cd(II) ions it was 19.79 mg/g onto KMBS at pH 9 and temperature 298 K. The sorption rate of Cr(VI) ions onto PBS increased sharply from 5 to 60 min and thereafter attained equilibrium. The same rapid sorption rates were observed for KMBS and H3 BS from 5 min and the processes were much faster and stabilized in 30 min. The sorption rates of Cd(II) ions were rapid from 5 min and remained significant until 60, 30 and 20 min mark for PBS, KMBS and H3 BS adsorbents respectively. Thereafter, little to no sorption was recorded for either adsorbents. Temperature increase had a positive effect on the uptake of Cd(II) and Cr(VI) ions onto all adsorbents. This was indicative of the endothermic nature. All the sorption processes of metal ions gave values that were positive for (ΔH o ) also suggesting that reactions were endothermic, and this was in agreement with temperature effect studies. It was observed that the uptake removal of Cd(II) and Cr(VI) ions found a good fit for PSO kinetic model. All metal ions sorption processes had positive (ΔS o ) values which indicates the increased randomness of the metal ions in the solution as the uptake processes approached equilibrium. Reusability test results showed that the pristine and modified adsorbents can be reused multiple times, showing the economic benefit of the adsorbents.